(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
The article speaks about artistic-aesthetic and methodological tasks of the narrative language is one of the important features of prose works. Also symbolic use of words related to colours is of particular interest. Observations show that in the prose works created in recent years, more attention has been paid to the symbolic expressions related to black